2000
DOI: 10.1001/archinte.160.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Are Genetic Influences on Peptic Ulcer Dependent or Independent of Genetic Influences for Helicobacter pylori Infection?

Abstract: Background: Genetic factors play a role or roles in the etiology of peptic ulcer disease and the acquisition of Helicobacter pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 31 publications
3
28
0
1
Order By: Relevance
“…[48] Malaty et al . [55] examined the longitudinal changes in H. pylori infection monitored from 1986-1994 within 46 families with children living in Japan. At study entry, prevalence of H. pylori in children with positive mothers was 23% versus 5% in children with negative mothers.…”
Section: Modes Of Transmissionmentioning
confidence: 99%
“…[48] Malaty et al . [55] examined the longitudinal changes in H. pylori infection monitored from 1986-1994 within 46 families with children living in Japan. At study entry, prevalence of H. pylori in children with positive mothers was 23% versus 5% in children with negative mothers.…”
Section: Modes Of Transmissionmentioning
confidence: 99%
“…A study of monozygotic and dizygotic twins reared together or reared apart, however, found that genetic influences for peptic ulcer were independent of genetic influences important for acquiring H pylori infection. Host genetics are probably less important than environmental factors or strain virulence in determining outcome [39].…”
Section: Host and Environmental Factors In H Pylori-related Ulcer Dismentioning
confidence: 99%
“…In virtually all of these children, inflammation of the gastric mucosa is present and caused by H. pylori infection [2][3][4][5]. Further evidence for the familial nature of primary gastritis and peptic ulceration in children is the clustering of H. pylori infection among family members [37][38][39][40]. More recently, work by El-Omar et al [41] has provided molecular evidence for the familial nature of gastric cancer associated with H. pylori infection.…”
Section: Overviewmentioning
confidence: 99%